Studying Religions with the Iron Curtain Closed and Open - Alles, Gregory D. (Method & theory in the study of religion, 2018)
This essay reflects especially on the insights that the volume under discussion offers to someone who grew up in the United States during the 1960s and for whom the region behind the Iron Curtain was largely unfamiliar territory. It notes the overarching political frame of the volume, both geographically—the study of religions in various nations—and chronologically—the study of religions in the pre-Communist, Communist, and post-Communist periods. It comments on the different political role that the study of religions played in Eastern Europe, where it contributed to movements of liberation, as distinct from the role it played in Western Europe and North America, where it was often the servant of colonialism. It also suggests that the volume leaves open for future research various questions about the enterprise of scientific atheism during the Communist period and its relation to the study of religions on both sides of the former Iron Curtain today.